Local Plant Motif of Kain Suket Ajang - Asrul Asshadi, Mohamad Morni; Mohd Azhar, Samin; Rafeah, Legino (2024)
This study delves into the identity of Suket Ajang, a traditional craft in Sarawak, particularly among Rajang's Melanau population. Employing semiotics, the research deciphers the complex meanings and cultural nuances embedded in Suket Ajang's native plant motifs. Through an in-depth examination of literary and visual materials, the study unveils the symbolic language within Suket Ajang, showcasing how individual motifs are chosen, investigated, and classified based on their semiotic qualities. This method sheds light on the aesthetic and semiotic elements, revealing the intricate blend of local plant features. Notable motifs like buwak tulau and tapok pedadah further contribute to Suket Ajang's rich cultural identity.